Redefining Spanish teaching and learning in the United States. (14th August 2018) - Pascual y Cabo, Diego; Prada, Josh
Abstract : This article describes a pedagogical initiative that identifies opportunities for increased efficiency and functionality in the teaching and learning of Spanish in the context of the United States. At the core of this initiative is the reformulation of curricular and programmatic approaches in terms of current social, cultural, and linguistic practices. More specifically, it combines and builds on insights from current theoretical and practical developments so as to do the following: (1) reconcile the currently conflicting educational goals of Spanish heritage language and foreign language teaching in the United States; (2) create a more sophisticated and efficient educational substructure than what is currently available to language learners of all profiles and levels; and (3) guide the allocation of resources to not only address and support heritage language maintenance and revitalization, but to also encourage a fortified stance on bilingualism and foster cultural richness/diversity among emergent bilinguals in foreign/second language programs. A rationale is offered, and the organization and processes involved in the implementation of this initiative are described, along with the possible beneficial academic, social, and community effects such a reformulation may yield. Challenges: Although the number of heritage speakers in language classrooms continues to grow, few substantial changes have been made regarding the overall orientation of Spanish teaching/learning. How can curriculum designers align learning experiences for heritage and foreign language learners? What pedagogical practices might support rich and well‐coordinated learning experiences for all students?